PENGARUH MOTIVASI INTRINSIK, DISILPIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BALI ADVENTURE TOURS - Ida Ayu Komang Juniasih; Ni Luh Ari Artini (Forum Manajemen STIMI Handayani Denpasar, 2021)
This study aims to determine the effect of intrinsic motivation, work discipline, and work environment on employee performance at PT Bali Adventure Tours. The population in the study were all employees of PT Bali Adventure Tours, totaling 109 respondents. Methods of data analysis using Validity Test, Reliability Test, Multiple Linear Regression Test, and Hypothesis Test (test). Based on the results of the analysis, it shows that intrinsic motivation has a significant positive effect on the performance of PT Bali Adventure Tours employees as indicated by the t-count value of 1.204 sig 0.001 and a significant value less than ¬a = ¬ 0.05 (0.001 <0.05). Work discipline has a significant positive effect on the employee performance of PT Bali Adventure Tours, indicated by the tcount value of 2.598 sig 0.001 and a significant value less than a = 0.05 (0.001 <0.05). The work environment has a significant effect on the employee performance of PT Bali Adventure Tours, indicated by the t-count value of 5.035 sig 0.000 and a significant value less than a = 0.05 (0.000 <0.05). The conclusion is that all independent variables have a positive and significant effect on the dependent variable. From the analysis, work environment variables have the most dominant influence on performance variables.